Hadith #2421 - Sunan Abi Dawud - Abu Ayyub al-Ansari; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Juwayriya bint al-Harith; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Do not fast on Saturday except what has been made obligatory on you; and if one of you can get nothing but a grape skin or a piece of wood from a tree, he should chew it.
Grade: Sahih